EFEKTIVITAS GAMES EDUCATION BERBANTUAN POHON ANGKA DALAM PENGENALAN ANGKA SISWA KELAS 1 SD NEGERI 04 MUNTOK - Imelda Ariana Marpaung; Sukardi; Eni Heldayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of game education with the help of number trees in the identification of 1st grade students of SDN 04 Muntok. This study uses a quantitative method of Quasi Experimental design experiment with pretest and posttest. The population of this study is all 1st grade students of SDN 04 Muntok, namely classes 1A and 1B totaling 40 people. The sampling technique used is purposive sampling. Based on the average posttest score obtained by the control class was 72.50 and the experimental class was 82.50. Hypothesis testing of the data of this study uses an independent sample t-test with hypothesis testing criteria, namely if the tcount > table. It was obtained with the values of tcal = 2.133 > ttable = 1.686 and sig. (2-tailed) = 0.039 < 0.05, then the calculation shows that Ha is accepted and Ho is rejected or the hypothesis states that it is proven that there is an effectiveness of games education with the help of number trees in the identification of 1st grade students of SDN 04 Muntok.